Migrant networks of irregular Nayu workers in Malaysia – The case of the Tom Yum restaurants in Kuala Lumpur - Suttiporn Bunmak, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
The Nayu workers are unauthorised foreign workers from Thailand who may be found operating and serving at the many Thai Halal Tom Yum restaurants all over Malaysia. This paper examines how migrant networks form and develop among Nayu migrants, former migrants and non-migrants in Thailand and Malaysia using data from ethnographic fieldwork. It is shown that international migration has increased in current years and unauthorised Nayu worker flow has become more complex because of the role migrant networks play in shaping migration connections between Thailand and Malaysia. Since they go through their contacts without using a recruitment agency, these pioneering migrants constitute a very important source of information about the availability of job opportunities in Malaysia. Newly arrived migrants are also initially assisted and settled by the pioneer migrants. In conclusion, the findings contribute important insights into the connections between the labour demands of the Tom Yum restaurant business in Malaysia and the labour supply of Nayu workers in Thailand.